(untitled) (Research, Society and Development, 2020)
Early Childhood Education is the first stage of basic education and comprises daycare and pre-school modalities. In Brazil, since 2013, the enrollment of children from 4 years of age in preschool has become mandatory. The objective of this work was to verify the growth curve of enrollments in Early Childhood Education in the public school system, between 2015 and 2018, in the State of Amapá-Brazil. The research has a quantitative and qualitative approach, as well as the procedure used, which was the collection of information at the electronic address of the National Institute for Educational Research Anísio Teixeira - INEP and the Brazilian Institute of Geography and Statistics - IBGE and bibliographic research. The results showed that for the period investigated (2015-2018) there was an increase in enrollments in Early Childhood Education in the public network of Amapá, but in special education offered in daycare centers, there was an oscillation for the period. It is concluded that the increase in the number of enrollments in Early Childhood Education is a positive factor, however, alone, it still does not cover the social demand for this segment. There is a need for reflection on financing in education, since those who have the lowest collection capacity, the municipalities, end up being responsible for the highest costs, Early Childhood Education and Elementary Education in the initial and final years.